2003
DOI: 10.1017/s1355617703910083
|View full text |Cite
|
Sign up to set email alerts
|

Are psychophysical functions derived from line bisection reliable?

Abstract: Psychophysical functions are used to characterize both normal perception and altered perception among patients with neglect, yet the reliability of these functions is rarely examined. The present study examined two-week, test-retest reliability for power functions derived from line bisection data among 58 normal, young and old, male and female subjects. Power function exponents and constants were, at best, moderately reliable over time. The size of the exponent tended to decrease at retesting. Reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Power functions applied to cancellation data show that the total number of cancellation targets predicts the number neglected (Chatterjee, Mennemeier, & Heilman, 1992b), regardless of the spatial location of neglected cancellation targets (Chatterjee, Mennemeier, & Heilman, 1992c), again suggesting that quantitative and spatial aspects of neglect are dissociable. Power functions account for extremely large portions of variance on all these tests in normal subjects and patients with neglect (Pierce et al, 2003;Mennemeier, Vezey, Lamar, et al, 2002;Chatterjee, 1995;Chatterjee, Dajani, et al, 1994;Chatterjee, Mennemeier, & Heilman, 1992a, 1992b. The quantitative errors made by patients with neglect appear to represent a true deficit in magnitude estimation because they are not merely restricted to estimates of length or to "spatial" stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Power functions applied to cancellation data show that the total number of cancellation targets predicts the number neglected (Chatterjee, Mennemeier, & Heilman, 1992b), regardless of the spatial location of neglected cancellation targets (Chatterjee, Mennemeier, & Heilman, 1992c), again suggesting that quantitative and spatial aspects of neglect are dissociable. Power functions account for extremely large portions of variance on all these tests in normal subjects and patients with neglect (Pierce et al, 2003;Mennemeier, Vezey, Lamar, et al, 2002;Chatterjee, 1995;Chatterjee, Dajani, et al, 1994;Chatterjee, Mennemeier, & Heilman, 1992a, 1992b. The quantitative errors made by patients with neglect appear to represent a true deficit in magnitude estimation because they are not merely restricted to estimates of length or to "spatial" stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due either to experimental factors such as the type of task (Rueckert et al, 2002) or nonexperimental factors such as the age or sex of subjects (Pierce et al, 2003), as such factors may influence attentional orientation and magnitude estimation. The truly novel finding of this study concerned the degree to which the physical presence of a line anchors attentional orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychophysical is a quantitative branch of the study of the perception, which evaluate the relations between observed stimuli and response and a form of measurement used in most psychophysical studies is through the reaction time 9,10 . In this task, the individual has to compare the order of presentation of two stimuli presented in the visual field at different intervals.…”
Section: Discussionmentioning
confidence: 99%